Chapter 7. Respiratory Diseases (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
AuthorMiss Aliya Rayyesa Mirzaa,PharmD Scholar, Department of Pharmacy Practice, Joginpally B.R. Pharmacy College, Telangana, IndiaAbstractPharmacological management of respiratory disorders requires targeted therapeutic approaches based on pathophysiological mechanisms and disease severity. Asthma treatment follows a stepwise approach utilizing inhaled corticosteroids, long-acting bronchodilators, and biological agents for specific phenotypes, with emphasis on device technique optimization and adherence monitoring. COPD management incorporates bronchodilator therapy, anti-inflammatory agents, and exacerbation prevention strategies based on symptom burden and risk assessment. Pulmonary infection treatment requires targeted antimicrobial selection considering local resistance patterns, disease severity, and patient risk factors. Sleep disorder interventions focus on underlying pathophysiology modification through pharmacological and mechanical approaches. Respiratory emergency management demands rapid assessment and intervention protocols incorporating bronchodilators, corticosteroids, and supportive measures. Treatment efficacy assessment utilizes objective measures including spirometry, symptom scores, and quality of life indicators.Keywords: Respiratory pharmacotherapy, Bronchodilator therapy, Antimicrobial selection, Sleep disorders, Emergency protocolsVIEW PDF